(untitled) (Conference Zone, 2022)
In our country, many laws, statutory legal-regulatory documents have been adopted in the field of construction in the field of environmental protection, rational use of natural resources, and ensuring environmental safety. The Law of the Republic of Uzbekistan "On Nature Protection" adopted on December 9, 1992 is the first legislative document in this direction after independence. As the population grows in the cities, the issue of environmental cleanliness emerges as the main problem in the field of urban planning and construction. It is important to have a completely new, full-fledged legal worldview, to know the laws of nature development in society and human activities, and to follow them in order to eliminate environmental stress in the field, to prevent environmental pollution.